Strategi Manajemen Sekolah dalam Penyelenggaraan Pendidikan Inklusif di SD Budimulia Muhammadiyah Adiwerna - Azizah, Nur Azizah; ibnu hasan, ibnu hasan; Darodjat, Darodjat (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
: SD Budi Mulia Muhammadiyah Adiwerna is a private school in Tegal Regency which has started implementing an inclusive education program. In carrying out this program, of course there are special strategies to optimize the inclusive education program. So this research was conducted to find out the strategies used br SD Budi Mulia Muhammadiyah in implementing the inclusive education program. This reseache uses qualitative field reseaech methode. Where this research used interview techniques eith subjects : 1 principal, 1 deputy principal, 2 shadow teachers and 1 parent of SD Budi Mulia Muhammadiyah Adiwerna. The result of this research state that there are four strategies implemented by Budi Mulia Muhammadiyah Elementary School, namely the Taman Bumimu approach, HR empowerment, learning methods and parent approach strategies.